Combining ruminally protected choline and flaxseed in cattle diets to increase the assimilation of omega-3 fatty acids from the diet - Caleb P. Weiss; Cadra L. Van Bibber-Krueger; K. A. Miller; Christian A. Alvarado-Gilis; James S. Drouillard (Kansas Agricultural Experiment Station Research Reports, 2014)
Omega-3 fatty acids are an essential part of a healthy human diet. If consumed regularly, these fatty acids attenuate inflammation and lower risk of inflammatory diseases, such as heart disease and rheumatoid arthritis. The human body cannot synthesize adequate amounts of omega-3 fatty acids; they must be obtained by consuming foods that are rich in omega-3s. Omega-3 fatty acids can be found in foods like fish, some oilseeds, and some nut oils. Overall consumption of these foods is relatively low compared with the consumption of red meat such as beef, which typically contains relatively small amounts of omega-3 fatty acids. Flaxseed contains high levels of omega-3 fatty acids, and when fed to cattle, these fats are absorbed and deposited into beef tissues. The transfer of omega-3 fatty acids from the diet to tissues is very poor, however, due to extensive alteration of fats by microbes in the rumen. If transfer efficiency from diet to tissues could be improved, beef could become a viable source of omega-3 fatty acids for consumers. Choline plays an important role in the metabolism of fats, and deficiencies of dietary choline could limit the absorption and tissue deposition of polyunsaturated fatty acids, including omega-3 fatty acids. Our objective was to evaluate the effects of combining ruminally protected choline and flaxseed on changes in plasma concentrations of long-chain fatty acids.
Keywords: Cattlemen' s Day; 2014; Kansas Agricultural Experiment Station contribution; no. 14-262-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1101; Beef Cattle Research; 2014 is known as Cattlemen' s Day; Beef; Omega-3 fatty acids; Choline; Flaxseed; Diet